2010
DOI: 10.1007/s00425-010-1218-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of molecular evolution and predicted function in thaumatin-like proteins of Populus trichocarpa

Abstract: Some pathogenesis-related proteins (PR proteins) are subject to positive selection, while others are under negative selection. Here, we report the patterns of molecular evolution in thaumatin-like protein (TLP, PR5 protein) genes of Populus trichocarpa. Signs of positive selection were found in 20 out of 55 Populus TLPs using the likelihood ratio test and ML-based Bayesian methods. Due to the connection between the acidic cleft and the antifungal activity, the secondary structure and three-dimensional structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…A study conducted on a total of 600 TLPs retrieved from 100 species in international databases revealed a cluster of phylogenetically related TLPs, enriched in poplar and tree sequences, that might represent a specific innovation in perennial species. Beyond the dramatic expansion of these defense-related genes in the poplar genome, diversification and subsequent sub- or neo-functionalisation likely occurred in poplar TLPs as exemplified by diversifying selection observed in this cluster [27, 28]. So far, other PR gene families have not been explored at the genome-wide scale in poplar, and it would be interesting to determine whether other expansions of specific gene family related to plant immunity occurred in trees, representing possible innovations in these long-living species.…”
Section: Learning From the Genomes Of Poplar And M Larici-populinamentioning
confidence: 99%
“…A study conducted on a total of 600 TLPs retrieved from 100 species in international databases revealed a cluster of phylogenetically related TLPs, enriched in poplar and tree sequences, that might represent a specific innovation in perennial species. Beyond the dramatic expansion of these defense-related genes in the poplar genome, diversification and subsequent sub- or neo-functionalisation likely occurred in poplar TLPs as exemplified by diversifying selection observed in this cluster [27, 28]. So far, other PR gene families have not been explored at the genome-wide scale in poplar, and it would be interesting to determine whether other expansions of specific gene family related to plant immunity occurred in trees, representing possible innovations in these long-living species.…”
Section: Learning From the Genomes Of Poplar And M Larici-populinamentioning
confidence: 99%
“…P. trichocarpa are reported to contain 42 TLP genes with diverse expressions in leaves infected with Melampsora spp (Rinaldi et al, 2007;Miranda et al, 2007;Azaiez et al, 2009;Petre et al, 2011). The length and physicochemical properties of the deduced proteins of PsTLP1 (245) and PsTLP2 (225) were consistent with most of the P. trichocarpa TLPs (~205-288 aa) (Zhao and Su, 2010;Petre et al, 2011). However, there were differences in the properties, such as pI, between PsTLP1 and PsTLP2 as well as different phylogenetic classification (in two groups).…”
Section: Discussionmentioning
confidence: 94%
“…The cocktail of proteins secreted into the rhizosphere comprises peroxidases [14,72,73], phosphatases [74,75], esterases [76], proteases [14,[77][78][79], chitinases [14,80], glucanases [14,81] and thaumatin-like proteins [1,82,83] ( Table 2). Some of these enzymes are members of a PR family [14].…”
Section: Proteomics Of Interactions Between Roots and Pathogenic Bactmentioning
confidence: 99%
“…In addition, it has been demonstrated that the transgenic plants were more resistant to abiotic stress [91]. The genes of these proteins are subject to selection, either positive or negative [83]. In Populus, a positive selection in 20 out of 55 thaumatin-like-proteins has been found [83].…”
Section: Proteomics Of Interactions Between Roots and Pathogenic Bactmentioning
confidence: 99%
See 1 more Smart Citation